The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1467-9817.2010.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Reading competence development of poor readers in a German elementary school sample: an empirical examination of the Matthew effect model

Abstract: According to the Matthew effect model, interindividual differences in reading competence between poor and normal readers should become wider as students grow older. The second part of the model assumes that these differential pathways are mainly attributable to differential reading activities. The purpose of this study is to examine whether both assumptions can be verified in a sample of German elementary school students. Data from 1,124 students, participating in the BiKS longitudinal study with assessment st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 29 publications
2
24
0
6
Order By: Relevance
“…Accordingly, researchers highlight the importance of school and classroom settings in the promotion of reading and suggest the implementation of programs that improve attitudes and beliefs by giving students successful reading experiences (McKenna et al 1995). This argument, which draws upon psychological research, is in line with current school effectiveness research in which student achievement is no longer viewed as the sole or most important educational goal (Krapp and Ryan 2002;Mullis et al 2006;Pfost et al 2012). Attitudes are considered important non-cognitive outcomes, which-taking an empirical perspective-have been investigated far less (Teddlie et al 2006).…”
Section: The Concept Of Reading Attitudes and Their Relation To Readimentioning
confidence: 60%
“…Accordingly, researchers highlight the importance of school and classroom settings in the promotion of reading and suggest the implementation of programs that improve attitudes and beliefs by giving students successful reading experiences (McKenna et al 1995). This argument, which draws upon psychological research, is in line with current school effectiveness research in which student achievement is no longer viewed as the sole or most important educational goal (Krapp and Ryan 2002;Mullis et al 2006;Pfost et al 2012). Attitudes are considered important non-cognitive outcomes, which-taking an empirical perspective-have been investigated far less (Teddlie et al 2006).…”
Section: The Concept Of Reading Attitudes and Their Relation To Readimentioning
confidence: 60%
“…Regarding implications for practice, our study showed that the ORF measure is an important developmental indicator of reading proficiency and is useful in monitoring students' reading fluency, which can help schools identify students who are at risk for reading failure (Fuchs et al., ; Pfost et al., ). In a prevention and early intervention framework of reading development, ORF is an efficient measure that schools can use to help teachers efficiently identify students who are on track and those who are not.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, it is one of the fundamental prerequisites for academic success, because proficient reading is of utmost importance for content learning in all educational subjects (Snow et al 1998;Retelsdorf et al 2012). Children begin learning to read systematically in elementary school, and thus, the acquisition of basic reading skills mainly takes place during the first years of schooling (for Germany: Klicpera and Gasteiger-Klicpera 1993;Pfost et al 2012). Later students develop more advanced reading skills such as text comprehension (Snow 2002).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Reading is an essential skill for academic achievement as well as for involvement in modern society (Snow et al 1998;Connor et al 2011;Pfost et al 2012). Thus, proficiency in reading, especially in reading comprehension, is of high importance to all students.…”
Section: Introductionmentioning
confidence: 98%